Characterization and expression of an endopolygalacturonase gene from a lupin anthracnose fungus identified as Colletotrichum lupine VAR. setosum - Berger, David Kenneth (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.